Empowerment in Mudarabah - Shaharuddin, A.; Gleave, R.E (Universiti Sains Islam Malaysia, 2024)
As one of the equity-based contracts in the Islamic commercial law, mudarabah has been viewed as the ideal basis for an interest-free banking operation. This article studies mudarabah theory as described by the great Muslim jurists. It examines the legal rulings of the four main madhahib namely the Hanafis, Malikis, Shafi'is and Hanbalis, and their relation to the financia1 practice of the mudarabah during the medieval period. The focus of discussion will be the scope of empowerment given by the investor to the agent-manager. It is found that the jurists differed in determining the restrictions to be placed upon the agent-manager in managing the capital entrusted to him. From a modern perspective, the Hanafis appeared to be the most flexible in comparison with the other three madhahib. In conclusion, the article will be a valuable addition to our understanding of mudarabah and perhaps, this will help us to develop a better equity-based financing instrument in the contemporary period.